Impact of Poor Pupillary Dilation on Intraoperative and Postoperative Outcomes in SICS - Dr V Keerthika; Dr Upagna Sanda (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Small Incision Cataract Surgery (SICS) is a cost-effective and widely practiced technique for cataract extraction in low-resource settings. However, performing SICS in patients with poorly dilated pupils presents technical challenges and increases the risk of complications. Understanding these risks is essential for better surgical planning and improved outcomes. Methods: This prospective observational study was conducted at a tertiary care teaching hospital in India and included 75 patients aged ≥40 years with senile cataract and inadequate pupillary dilation (<5 mm) after standard mydriatics. Patients underwent SICS with pupil management techniques such as stretch pupilloplasty, sphincterotomies, iris hooks, or expansion rings. Intraoperative and postoperative complications were recorded and analyzed using descriptive statistics and chi-square tests. Results: The most common causes of poor pupil dilation were pseudoexfoliation syndrome (28%) and diabetes mellitus (22.7%). Intraoperative complications were observed in 52% of patients, with difficult nucleus delivery (16%) and iris trauma (13.3%) being the most frequent. Postoperatively, anterior chamber inflammation (26.7%) and corneal edema (18.7%) were common. A statistically significant association was found between pupil management technique and intraoperative complications (p = 0.041), and between intraoperative complications and poorer visual outcomes (p = 0.002). At 4 weeks, 64% of patients achieved a best-corrected visual acuity (BCVA) of ≥6/12. Conclusion: SICS in poorly dilated pupils is associated with increased surgical complexity and a higher risk of complications. However, with appropriate pupil management techniques and surgical expertise, satisfactory visual outcomes can be achieved. Early identification of risk factors and tailored surgical strategies are critical for optimizing patient care.